Socio-Political Problems Of Women In Assam: Issues Of Identity, Violence And Development - Dr. Sanjay Mili (Elementary Education Online, 2021)
This research article examines the multifaceted socio-political problems faced by women in Assam, with a focus on issues of identity, violence, and development. Assam, a state in northeastern India, presents a complex socio-cultural landscape where women encounter numerous challenges. The article explores how women in Assam grapple with issues of identity, often navigating multiple cultural and social identities that intersect with their gender. It also delves into the prevalence of various forms of violence against women in the region, including domestic violence, sexual assault, and trafficking, and the impact of these on women's lives and well-being. Furthermore, the article analyzes the role of development initiatives and policies in addressing these challenges, highlighting both successes and shortcomings. Through a comprehensive analysis, the article aims to contribute to a deeper understanding of the socio-political dynamics affecting women in Assam and to inform more effective strategies for addressing their issues.